2020
DOI: 10.26452/ijrps.v11i2.2080
|View full text |Cite
|
Sign up to set email alerts
|

Role of insulin/insulin-like growth factor-1 signaling pathway genes on the lifespan of Caenorhabditis elegans

Abstract: Aging process is influenced by the insulin/insulin-like growth factor-1 signaling (IIS) pathway or IGF-1 signaling pathway. Studies done on the genes of this pathway were found to affect longevity. However, no conclusive results have been drawn.The purpose of this systematic review is to summarize the function of genes involved in the IIS pathway of Caenorhabditis Elegans (C. elegans), a nematode commonly used as a model organism in molecular genetics and developmental biology. A literature search for relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The IIS pathway regulates metabolism, growth, and life span by detecting nutrient levels. Studies conducted on IIS pathway suggested an inverse correlation between IIS pathway activation and life span extension (Zulkefli, Shuid, & Aan, 2020). Similarly, the attenuation of mTOR signalling pathway, which regulates cell survival and growth, also contributes to life span extension in model organisms (Antikainen, Driscoll, Haspel, & Dobrowolski, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The IIS pathway regulates metabolism, growth, and life span by detecting nutrient levels. Studies conducted on IIS pathway suggested an inverse correlation between IIS pathway activation and life span extension (Zulkefli, Shuid, & Aan, 2020). Similarly, the attenuation of mTOR signalling pathway, which regulates cell survival and growth, also contributes to life span extension in model organisms (Antikainen, Driscoll, Haspel, & Dobrowolski, 2017).…”
Section: Introductionmentioning
confidence: 99%